EVALUASI WAKTU DAN BIAYA INSTALASI DAMPER PADA PROYEK COMBINE CYCLE PLTGU - Fikri, Muhammad .; Madelan, Sugiyono . (Universitas Mercu Buana, 2019)
Abstract. The increasing need for electricity has made the construction of many power plants a lot. To support the program, it is expected that there will be no delay in completing the construction of an additional 650 MW of Gas Power Plant in Muara Tawar. In addition, the damper installation is needed as the initial work that is very influential on other jobs. In the installation of a damper for unit 2.1 there was a delay of installation for 6 days from a predetermined schedule. Evaluation of the delay is done by scheduling the CPM (Critical Path Method) method to determine the critical path and accelerate the project by using the crashing method in addition to working hours. By using the CPM method, it was found that the critical time of the installation work was 272 hours and using the crashing method in addition to working hours which were initially 272 hours to 244 hours, there was a crashing cost of Rp 6,868,300.